SURVEY OF CHANGES IN COMPLETE BLOOD COUNT AND RED CELL INDICES OF WHOLE BLOOD INCUBATED IN VITRO AT DIFFERENT TEMPERATURES UP TO 48 HOURS - Mahmoodi, Mehdi; Hajizadeh, Mohammareza; Rashidinejad, Hamidreza; Asadikaram, Gholamreza; Khaksari, Mohammad; Mirzaee, Mohammadreza; Seyedi, Naser; Rahnema, Amir; Sayadi, Ahmadreza (Journal of Ayub Medical College Abbottabad, 2006)
Background: Complete blood count (CBC) is one of the most common and conventional blood test that physicians usually request. However the results of this test are affected by different factors such as, the temperature and duration of incubation, therefore the aim of this survey was to evaluate the effect of temperature and time of incubation on CBC, red blood cells (RBC) indices and white blood cells (WBC) differential count. Methods: In a cross-sectional study, blood samples were taken from 30 healthy medical students of Rafsanjan University (15 males and 15 females). The samples divided into three parts; CBC were done on the samples up to 48 hours incubation at temperature of 25, 30, and 370 C at the time of sampling, and after 2, 8, 24 and 48 hours. Data were statistically analyzed and the following results were obtained. Results: RBC count, hematocrit, MCH, percent of monocytes and eosinophils were constant in different temperatures, WBC count, MCHC, hemoglobin, platelets count, the percent of lymphocytes and neutrophils were constant up to 24 hours and then tend to increase with increasing temperature except lymphocytes percent that tend to decrease. MCV decreased with increasing temperature up to 8 hours and then significantly increased (from 83.89 to 87.50 fmol/l, p<0.001). WBC, hematocrit, MCV, platelets count, and neutrophils’ percent tend to increase by the time of incubation, but RBC count, MCHC, lymphocytes’ percent decreased. Hemoglobin, MCH, and the percent of monocytes and eosinophils were constant. Conclusion: The finding of this survey showed that some of CBC parameters can be changed with the incubation, therefore it is better to do the CBC test after blood taking as soon as possible. Key Words: CBC, RBC Indices, Temperature of storage, Time of storage